Energy efficiency in delay-limited and delay-tolerant transmission mode, with N = 4, m = 1, = 2/3, = 10 dBw, = 4 dBw, = 10 dBm, = 10 dBm and = 10 dBm. - Minh Tran (7698803) (2025)
Energy efficiency in delay-limited and delay-tolerant transmission mode, with N = 4, m = 1, = 2/3, = 10 dBw, = 4 dBw, = 10 dBm, = 10 dBm and = 10 dBm.